Islamic Education According to Ramli Abdul Wahid - Aldiansyah Aldiansyah; Usiono Usiono; Azizah Hanum OK (Universitas Muhammadiyah Enrekang, 2024)
In the past, the habit of writing among ulama was deeply rooted in various scientific disciplines, especially religious sciences. No doubt, it is this habit of writing that has encouraged the rapid development of knowledge in Islamic education. Therefore, this scientific study aims to examine in more depth the thoughts on Islamic education based on the work written by Prof. Dr. Ramli Abdul Wahid, MA. This scientific study uses the Systematic Literature Review (SLR) method with PRISMA analysis. The results of the analysis state that in his perspective, Prof. Ramli views Islamic education as education based on the Al-Qur'an and Hadith. However, the delay in the study of hadith in Indonesia has had a significant impact on the progress of thinking among Muslims. This is because Islamic education, especially the science of hadith, is very closely related to the living conditions of Muslims in every era or civilization. Therefore, awareness and the active role of various parties and contemporary Islamic educational institutions are urgently needed, so that they can become a means of developing and studying Islamic education in Indonesia